A Performer's Guide to Seventeenth-Century Music, Second Edition - Kite-Powell, Jeffery T.; Carter, Stewart, 1944- (Book collections on Project MUSE., 2012)
"Revised and expanded, A Performer's Guide to Seventeenth Century Music is a comprehensive reference guide for students and professional musicians. The book contains useful material on vocal and choral music and style; instrumentation; performance practice; ornamentation, tuning, temperament; meter and tempo; basso continuo; dance; theatrical production; and much more. The volume includes new chapters on the violin, the violoncello and violone, and the trombone--as well as updated and expanded reference materials, internet resources, and other newly available material. This highly accessible handbook will prove a welcome reference for any musician or singer interested in historically informed performance."--Provided by publisher.